2021
DOI: 10.1186/s12885-021-07971-w
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab Emtansine (T-DM1) and stereotactic radiation in the management of HER2+ breast cancer brain metastases

Abstract: Background Due to recent concerns about the toxicity of trastuzumab emtansine (T-DM1) with stereotactic radiation, we assessed our institutional outcomes treating HER2-positive breast cancer brain metastases (BCBM) with T-DM1 and stereotactic radiation. Methods This is a single institution series of 16 patients with HER2-positive breast cancer who underwent 18 stereotactic sessions to 40 BCBM from 2013 to 2019 with T-DM1 delivered within 6 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…Stereotactic radiation technique was conducted as previously described [ 13 , 14 ]. Brain metastases were assessed using magnetic resonance imaging (MRI) (Siemens Sonata, Siemens Medical Systems, Erlangen, Germany) with 1 mm slices for treatment planning purposes prior to the delivery of radiation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stereotactic radiation technique was conducted as previously described [ 13 , 14 ]. Brain metastases were assessed using magnetic resonance imaging (MRI) (Siemens Sonata, Siemens Medical Systems, Erlangen, Germany) with 1 mm slices for treatment planning purposes prior to the delivery of radiation.…”
Section: Methodsmentioning
confidence: 99%
“…Patients in this study were followed with examinations by the treating radiation oncologist, neurosurgeon, and/or medical oncologist and with MRI imaging at 2–3-month intervals [ 13 ]. At each visit neurologic status was assessed.…”
Section: Methodsmentioning
confidence: 99%
“…In a separate report, RN was observed in 40% of patients that received T-DM1 [40]. In contrast, Mills et al reported that the combination of SRS and T-DM1 was well tolerated, with only 3% of patients reporting RN [41]. Hence, prospective studies to evaluate the ideal dose of SRS and timing of T-DM1 are warranted.…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…For this reason, utilization of this drug decreased given that SRS is a mainstay of therapy for patients with brain metastases. However, a recent study by Mills at al reporting on a single institution series of 16 patients with HER-2 positive breast cancer who underwent SRS and T-DM1 therapy delivered within 6 months showed only 1 case (3%) of symptomatic radionecrosis (39). The authors hypothesized that those prior studies showing increased rates of radionecrosis included longer time intervals from radiation and potentially do not accurately reflect toxicity from the combined treatment.…”
Section: Breast Cancermentioning
confidence: 99%